Two Sides, Same Coin: Posttraumatic Growth Among Selected Nurses with History of Covid-19 Virus in Bataan, Philippines - Ronnel Magpantay; Jayvie Villazor (GLOBAL HEALTH SCIENCE GROUP, 2025)
Over the past three years, the pandemic has substantially altered the field of healthcare. Consequently, the general well-being of nurses was negatively impacted as a result of this change. It affects both their professional and personal lives, specifically their psychological, social, and physical sequelae. However, positive transformation, also known as posttraumatic growth, is possible. In the current study, the objective is to provide an account and analysis of the essence of the experience of posttraumatic growth among nurses after being exposed to COVID-19 during the pandemic. Twelve participants from Bataan, Philippines, were interviewed in person using a semi-structured interview format based on descriptive phenomenology. The study's findings unveiled three distinct themes, each of which possesses its own complementary opposition. One of the dichotomies is referred to as